2018
DOI: 10.2807/1560-7917.es.2018.23.30.1700777
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for colistin-resistant Enterobacteriaceae in a low-endemicity setting for carbapenem resistance – a matched case–control study

Abstract: BackgroundEmergence of colistin resistance has been related to increased use in clinical settings, following global spread of carbapenem-resistant Gram-negative bacteria. Use of colistin in animal production may constitute a further source of spread of resistant strains to humans. We sought to determine risk factors for human colonisation or infection with colistin-resistant Escherichia coli and Klebsiella pneumoniae in a setting where colistin is mainly used for animal production. Methods: This retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Independent risk factors for isolation of CORE and COSE in this study were similar. This echoes prior data from Europe, where the characteristics of patients with colistin-resistant and colistin-susceptible E. coli or K. pneumonia did not differ; prior meropenem exposure was the only variable uniquely associated with colistin-resistant isolates [ 14 ]. Of note, meropenem use was uncommon in our current cohort.…”
Section: Discussionsupporting
confidence: 79%
“…Independent risk factors for isolation of CORE and COSE in this study were similar. This echoes prior data from Europe, where the characteristics of patients with colistin-resistant and colistin-susceptible E. coli or K. pneumonia did not differ; prior meropenem exposure was the only variable uniquely associated with colistin-resistant isolates [ 14 ]. Of note, meropenem use was uncommon in our current cohort.…”
Section: Discussionsupporting
confidence: 79%
“…In recent years, to tackle the rapid increase in prevalence of carbapenem-resistant isolates in human infections, the use of the relatively toxic polymyxins has become more frequent, and multiple studies from various parts of the world have also confirmed the parallel increase in dissemination of colistin-resistant isolates in wastewater and water bodies [41][42][43][44][45]. Regardless of an increase in polymyxin sales in India between 2000-2015 [4], data on dissemination has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The mcr-1 gene can be transmitted through the plasmid to colistin-sensitive strains. [33][34][35][36] Another concern is the emergence of colistin resistance during therapy among KPCproducing strains of P. aeruginosa in Switzerland, 37 USA, 38 and Australia. 8 As the main benefit of this study was to develop an HRMA assay to detect low levels KPC-producing, ESBL producing simultaneously, and CRPA strains, we next selected the KPC/IMP/mprA primer set1 and TEM/ SHV/mcr-1 primers set2 combination for a multiplex assay assessment.…”
Section: Dovepressmentioning
confidence: 99%